Strategi Local Strongman dalam Pemilihan Kepala Desa Bumi Sari Kecamatan Natar Kabupaten Lampung Selatan tahun 2019 - Erlangga Satria Agung; Himawan Indrajat; Budi Harjo; Bendi Juantara (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: this study is to find out how the local strongman strategy in winning the candidate for the head of the village. Bumi Sari Village, Natar District, South Lampung Regency. Method: The researchers used the local strongman theory through an offensive and defensive strategy approach. Both of these strategies will be used to understand this phenomenon. The type of research used is qualitative research by conducting interviews with people involved in the election of the head of Bumi Sari Village. Result: The results of the election for the head of Bumisari Village in 2019 won Yosar Supriyono as the village head, Yosar Supriyono was re-elected as the head of the Bumisari village in 2019. Supri's victory could not be separated from the support of the local Strogman. The involvement of the local strongman in the village head election makes it interesting to see how the local strongman strategy in an effort to win Yosar in the village head election in Bumisari in 2019. Contribution: 1. Delegating a team of experts in the field of village politics to find out the vote map, 2.Forming groups of successful teams so that they can be closer and in direct contact at all levels.community activities.